The city of Arbes is a study of its general conditions from the Islamic conquest of Morocco Until the end of the fifth century AH / eleventh century AD (Journal of the College of Basic Education, 2022)
Researching the history of cities, especially the unknown ones, is one of the things that appeals to the researcher in order to shed light on these cities and highlight their role throughout history. Throughout history, especially since the city was a military base from which armies set out to open cities throughout its eras, in addition to the economic and commercial activities that the city enjoys with other Moroccan cities, as well as its scientific activities and its most famous scholars who excelled in religious forensic sciences, linguistic sciences and pure sciences.